Faith in the just behavior of the government: intergroup apologies and apology elaboration - Steele, Rachel; Blatz, Craig (My University, 2014)
After intergroup injustices, perpetrator groups may seek to restore intergroup relations by offering an apology. Through quantitative empirical tests some scholars have examined whether these apologies promote forgiveness and reconciliation. This work has found inconsistent relations between apology and forgiveness. We proposed and tested other variables as relevant outcomes of intergroup apology as well, namely perceived remorsefulness, faith in societal norms of justice, and trust. We also tested how the elaborateness of an apology changed its effectiveness. The study (N = 145) presented excerpts of President Clinton’s apology for the Tuskegee Syphilis Study to African-Americans, varying the apology elaborateness. We examined whether apologies of varying elaborateness affect forgiveness (to be consistent with past research), perceptions that the response was remorseful, beliefs that norms of just behavior would be upheld, and trust in the perpetrator group. All apologies, but particularly more elaborate apologies, resulted in higher perceptions of remorsefulness and justice norms, but not trust or forgiveness. The results imply that apologies may have many benefits with perceptions of remorsefulness and justice norms being amongst them.
Keywords: apology; elaboration; intergroup apology; intergroup relations; justice norms; perceived remorsefulness; restorative justice